Implementasi Program SAPAMAT untuk Meningkatkan Pemahaman Siswa Kelas IV pada Materi Bangun Datar - Kusuma, Lintang Pandu; Irawati, Riana; Syahid, Aah Ahmad (Jurnal Kridatama Sains dan Teknologi, 2024)
Mathematics is an important subject to apply. Therefore, mathematics is taught at every level of education. Mathematics is widely used in everyday life. Many people assume that mathematics is a troublesome illustration, this assumption has been passed down from time to time, so that the mentality towards mathematics is always considered troublesome. This is also experienced by fourth grade students of SD Negeri 3 Tugu and SD Negeri Pakuran who have difficulty learning mathematics on plane geometry material. Based on the results of initial observations on fourth grade students of SD Negeri 3 Tugu and SD Negeri Pakuran, students have difficulty in plane geometry material which includes properties, composition, decomposition of plane geometry. Understanding the concept and remembering the properties of plane geometry is often a challenge for students. Therefore, the SAPAMAT program is used in this study to help fourth grade students understand plane geometry material better. The SAPAMAT program stands for the Mathematics Breakfast Program or can be called morning lessons. This study uses the Quasi Experiment method with the Nonequivalent Control Group Design model. This study uses 2 groups, namely the experimental class group and the control class group. Pretest and posttestare the methods used to collect data. Normality test, homogeneity test, average difference test, and n-gain test are the data analysis methods used. The results of the statistical analysis of the average gain value of the experimental class are 0.78 while the control class is 0.31. This is reinforced by the average gain difference test, namely the sig p-value of 0.000. P-value 0.000 <0.05 so that H0 is rejected and H1 is accepted. This means that there is a difference in the increase in the abilities of students in the experimental class and the control class. Therefore, it can be concluded that the SAPAMAT program has an effect on increasing the understanding of grade IV students in the material of flat shapes